2023
DOI: 10.1038/s43018-023-00563-6
|View full text |Cite
|
Sign up to set email alerts
|

Limiting mitochondrial plasticity by targeting DRP1 induces metabolic reprogramming and reduces breast cancer brain metastases

Abstract: Disseminated tumor cells with metabolic flexibility to utilize available nutrients in distal organs persist, but the precise mechanisms that facilitate metabolic adaptations remain unclear. Here we show fragmented mitochondrial puncta in latent brain metastatic (Lat) cells enable fatty acid oxidation (FAO) to sustain cellular bioenergetics and maintain redox homeostasis. Depleting the enriched dynamin-related protein 1 (DRP1) and limiting mitochondrial plasticity in Lat cells results in increased lipid droplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…These results were seen across the spectrum of PCa progression, from benign to late-stage, 2D and 3D models. Importantly, the magnitude of exogenous FA enrichment into citrate was comparable to similar studies, including ∼15% in ex vivo cultured malignant Patient-Derived Xenografts (500 μM [U- 13 C]palmitate, 4 hours) 6 and BT549 cells (100 μM [U- 13 C]palmitate, 24 hours) 21 , <15% in HCC1954 and SKBR3 breast cancer cells (100 μM [U- 13 C]palmitate, 24 hours) 58 , and ∼10% in MCF-7 and MDA-MB-231 breast cancer cells cultured in glucose-free media (100 μM [U- 13 C]palmitate, 4 hours) 59 . Therefore, these observations raise questions regarding the many studies demonstrating that CPT1 loss-of-function leads to cell death 19,60 .…”
Section: Discussionsupporting
confidence: 74%
“…These results were seen across the spectrum of PCa progression, from benign to late-stage, 2D and 3D models. Importantly, the magnitude of exogenous FA enrichment into citrate was comparable to similar studies, including ∼15% in ex vivo cultured malignant Patient-Derived Xenografts (500 μM [U- 13 C]palmitate, 4 hours) 6 and BT549 cells (100 μM [U- 13 C]palmitate, 24 hours) 21 , <15% in HCC1954 and SKBR3 breast cancer cells (100 μM [U- 13 C]palmitate, 24 hours) 58 , and ∼10% in MCF-7 and MDA-MB-231 breast cancer cells cultured in glucose-free media (100 μM [U- 13 C]palmitate, 4 hours) 59 . Therefore, these observations raise questions regarding the many studies demonstrating that CPT1 loss-of-function leads to cell death 19,60 .…”
Section: Discussionsupporting
confidence: 74%
“…reported that targeting mitochondrial plasticity by knocking down DRP1 expression and inhibiting MDIVI1 attenuates oncosphere formation and reduces the brain metastatic potential of Lat and M-BM cells in preclinical models. 36 In addition, several studies have reported that FDA-approved drugs Leflu and Teri promoted mitochondrial fusion 15 , 20 , 37 and can influence DRP1. Our molecular modeling of the interaction of DRP1 with Leflu, Teri, and MDIVI1 revealed that Teri had the highest binding score, Leflu showed a less robust interaction, and MDIVI1 showed the lowest binding score.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells can utilize FAs received from their environments, including the bloodstream ( Koizume and Miyagi, 2016 ), cancer-associated fibroblasts ( Hwang et al, 2022 ), reactive astrocytes ( Parida et al, 2023 ), and adipocytes ( Nieman et al, 2011 ), and/or synthesized by themselves ( Koizume and Miyagi, 2016 ; Cruz et al, 2020 ). FAs are a source of ATP produced through FAO in mitochondria, followed by oxidative phosphorylation.…”
Section: Effect Of Fa Oxidation On Cancer Progression and Its Correla...mentioning
confidence: 99%